2013
DOI: 10.3342/kjorl-hns.2013.56.5.286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Taste Thresholds in Korean

Abstract: Background and ObjectivesZZThe sense of taste is one of the most important human senses and plays a critical role in an individual's food preferences and the nutritional status. Proper gustatory function in older people is important for quality of life and enjoyment of food. The objectives of this study was to investigate the effect of aging on taste thresholds in Korean subjects. Subjects and MethodZZOne hundred sixty normal volunteers without smell and taste disorders were investigated. Each subject was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Effects of aging on sweet threshold values reported in the literature varied among studies. Increases in sweet threshold values have been reported previously in Japanese (Fukunaga et al, 2005;Ogawa et al, 2017) and Korean elderly subjects (Lee et al, 2013). Yoshinaka et al (2015) found no difference in sweet recognition thresholds between Japanese subjects of ages 24-32 and 69-71 years, however, an increase in threshold value was observed after 79 years of age.…”
Section: Bet Valuesmentioning
confidence: 62%
See 4 more Smart Citations
“…Effects of aging on sweet threshold values reported in the literature varied among studies. Increases in sweet threshold values have been reported previously in Japanese (Fukunaga et al, 2005;Ogawa et al, 2017) and Korean elderly subjects (Lee et al, 2013). Yoshinaka et al (2015) found no difference in sweet recognition thresholds between Japanese subjects of ages 24-32 and 69-71 years, however, an increase in threshold value was observed after 79 years of age.…”
Section: Bet Valuesmentioning
confidence: 62%
“…The threshold values tended to increase further in the elderly, albeit not significant ( p > .05). Increases in threshold value of NaCl with aging have been reported in Caucasian (Mojet et al, ), Japanese (Fukunaga et al, ; Yoshinaka et al, ), and Korean (Lee et al, ) subjects. Ogawa et al () suggested that cognitive status was the major factor affecting salty taste sensitivity in the elderly since elderly subjects with lower cognitive scores showed a significantly greater decline in salty taste perception.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations